2007
DOI: 10.1124/jpet.107.126540
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Phosphodiesterase-5 (PDE5) Catalytic Site to Higher Affinity by PDE5 Inhibitors

Abstract: Phosphodiesterase-5 (PDE5) specifically hydrolyzes cGMP, thereby contributing to modulation of intracellular levels of this nucleotide. In the present study, preincubation with cGMP increased PDE5 catalytic activity for cGMP degradation, and it converted the PDE5 catalytic site to a form that was more potently inhibited by each of the three PDE5 catalytic sitespecific inhibitors: sildenafil, vardenafil, and tadalafil. These results implied that elevated cGMP initiates a physiological negative feedback on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 34 publications
1
20
0
2
Order By: Relevance
“…This method was also applied for two other PDE5 inhibitors (vardenafil and tadalafil). The ratio between fast and slow components varied between PDE5 inhibitors and could be changed by long preincubation with PDE5 inhibitors (Blount et al, 2007). For example, 12-h preincubation with 30 nM tadalafil resulted in detection of only the slow (high-affinity) component for full-length PDE5 and for a construct containing GAF-B and the catalytic domain but not for the catalytic domain alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method was also applied for two other PDE5 inhibitors (vardenafil and tadalafil). The ratio between fast and slow components varied between PDE5 inhibitors and could be changed by long preincubation with PDE5 inhibitors (Blount et al, 2007). For example, 12-h preincubation with 30 nM tadalafil resulted in detection of only the slow (high-affinity) component for full-length PDE5 and for a construct containing GAF-B and the catalytic domain but not for the catalytic domain alone.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not clear why PDE5 retains sildenafil for 12 to 24 h after taking one dose of sildenafil. Studies of sildenafil dissociation patterns showed that only long preincubation with high concentrations of PDE5 inhibitors could substantially slow down dissociation (Blount et al, 2007). In addition, sildenafil as a moderately lipophilic compound is expected to achieve equilibrium between its intracellular and extracellular/plasma concentrations relatively fast.…”
Section: Discussionmentioning
confidence: 99%
“…The basal affinity of PDE5 for the inhibitors, which is intrinsically high (K D ¼ 0.1-4 nM), can increase further in response to elevation of cGMP as would occur with sexual stimulation 12 and/or prolonged exposure to the respective drugs. 54 As discussed below, this increased affinity is caused by allosteric binding of cGMP to PDE5, increased phosphorylation of the enzyme and prolonged perturbation of the catalytic site of the enzyme by elevated cGMP and inhibitor. 9,11,12,55 Therefore, a few hours after ingestion of a PDE5 inhibitor either in the presence or absence of sexual arousal, plasma inhibitor concentration would be high and it is predicted that the catalytic site of PDE5 in VSMC would be saturated with inhibitor and that the affinity of PDE5 for the inhibitor would be significantly higher than in the basal state (Figure 4b).…”
Section: Retention Of Pde5 Inhibitors In Vsmc After Clearance From Plmentioning
confidence: 99%
“…An important correlate is that when a PDE5 inhibitor is present, these same mechanisms result in enhanced binding affinity of the catalytic site to the inhibitor, perhaps enhancing and prolonging its efficacy. 48 It is presumed this also provides a molecular mechanism for rapid cGMP oscillations to occur in response to rapid changes in NO or ANP, though it remains unclear how this could operate given the very high affinities measured for cGMP binding in vitro. It seems likely that another layer of regulation of cGMP binding affinity exists but has yet to be elucidated.…”
Section: Function Of Bindingmentioning
confidence: 99%